Nurses’ Knowledge and Attitudes Regarding Children’s Pain Assessment and Management in Nepal - Shrestha-Ranjit, Jagamaya; Ranjitkar, Uma Devi; Water, Tineke; Shrestha, Sulochana; Sharma, Chandrakala; Mukhia, Suzanna; Adhikari, Jamuna; Adhikari, Tulashi; Pandey, Archana; Sharma, Muna; Pandey, Apsara; Joshi, Nibaran; et al. (SAGE Publications, 2023)
Pain is frequently experienced by children in hospital, and international guidelines for appropriate pain assessment and management are available. Optimal management of paediatric pain has important long-term health, psychosocial, and economic benefits. However, evidence indicates that globally there are deficits in nurses' understanding of paediatric pain assessment and management. This study explored knowledge and attitudes regarding paediatric pain assessment and management among nurses at a tertiary children's hospital in Nepal. In this cross-sectional study all 140 nurses at a tertiary children's hospital in Nepal, were invited to complete the validated Paediatric Nurses Knowledge and Attitudes Survey. Findings revealed substantial deficits in nurse's knowledge and erroneous attitudes towards pain assessment and management in children. Test scores ranged from 14% to 56%, with mean scores of 38%, with no nurses achieving a recommended pass score of 80% regarding knowledge and attitudes in paediatric pain management. Consistent with previous research, nurses had insufficient knowledge and attitudes that did not reflect best practice regarding pain assessment and management in children. Education programmes targeting both trainees and registered nurses are essential to enable nurses to deliver evidence-based care and improve outcomes for children and their families.
Keywords: Child; education; infant; low- and middle-income countries; Nepal; nursing knowledge; paediatric nursing; pain management; pain measurement; Child; Nepal; education; infant; low- and middle-income countries; nursing knowledge; paediatric nursing; pain management; pain measurement; 4203 Health Services and Systems; 4205 Nursing; 42 Health Sciences; Chronic Pain; Pediatric; Clinical Research; Pain Research; 8.1 Organisation and delivery of services; 7.1 Individual care needs; 7.3 Management and decision making; 1110 Nursing; 1114 Paediatrics and Reproductive Medicine; 1117 Public Health and Health Services; 3213 Paediatrics; 4205 Nursing